Zinc Status of Horses and Ponies: Relevance of Health, Horse Type, Sex, Age, and Test Material - van Bömmel-Wegmann, Sarah; Gehlen, Heidrun; Barton, Ann-Kristin; Büttner, Kathrin; Zentek, Jürgen; Paßlack, Nadine; Justus Liebig University Giessen (My University, 2023)
Little is known about the animal- and diet-related factors that could interfere with the plasma zinc (Zn) concentrations of equines. Additionally, the adequacy of plasma to reflect changes in the Zn intake is unclear. In the first part of this study, the plasma Zn concentrations of hospitalized horses and ponies (n = 538) were measured and evaluated for the impact of the age, sex, horse type, and internal diseases of the animals. In the second part, the effects of increasing dietary Zn chloride hydroxide and Zn methionine supplementations were assessed on the plasma and mane hair Zn concentrations of healthy horses (n = 2) and ponies (n = 8). Part 1: The age, sex, and horse type did not influence the plasma Zn concentrations. No effect of internal diseases was observed, with the exception of higher plasma Zn concentrations in animals with metabolic disorders compared to the control group (p < 0.05). Part 2: Both Zn supplements dose-dependently increased the Zn concentrations in the mane hair (p = 0.003), but not in the plasma of the horses and ponies. In conclusion, the plasma Zn concentrations were widely unaffected by nutritional and non-nutritional factors in equines, while mane hair samples better reflected the dietary Zn supply.
Keywords: zinc; diet; equines; plasma; mane hair; age; sex; ddc:630